Keterkaitan Spasial Kabupaten/Kota Berdasarkan Sektor Unggulan di Provinsi Jawa Barat Tahun 2017-2021 - Nisa Nurokhati; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2023)
This study aims to analyze the spatial linkages between districts/cities based on leading sectors in West Java Province. This study uses the Location Quotient (LQ) analysis method and Spatial Autocorrelation analysis using the Global Moran analysis tool and the Local Indicator of Spatial Autocorrelation (LISA). This study uses secondary data in the form of Gross Regional Domestic Product (GDP) data based on constant prices according to the district/city business field of West Java Province for 2017-2021 sourced from the Badan Pusat Statistik of West Java Province. The results of calculating the LQ index which forms the basis of Global Moran and LISA analysis show that there are three highest leading sectors in West Java, namely the construction sector; government administration sector, defense, and mandatory social security; as well as the education services sector. Based on the results of Global Moran's analysis of the 3 leading sectors, only the government administration, defense, and compulsory social security sectors and the education services sector have significant spatial linkages in West Java. However, the area disturbance is classified as weak because the Moran index value is away from the value (+1). The results of the Local Indicator of Spatial Autocorrelation (LISA) analysis show cluster patterns and High-High (Hot-Spot) interplay in the defense administration, defense, and mandatory social security sectors in Ciamis Regency and the education services sector in Ciamis Regency, Majalengka Regency, and Kuningan Regency. The limitation of this research is that Global Moran and LISA analyses only use a significance test of α = 5% so the interpretation of inter-regency/city linkages is still lacking in detail.